2017
DOI: 10.1002/jsfa.8531
|View full text |Cite
|
Sign up to set email alerts
|

Balanced N and C input recommendations for rain‐fed maize production in northern China based on N balances and grain yields

Abstract: The study suggests that N balances close to neutral be given priority to improving N-use efficiency, and more positive C balances also be important for sustaining target yields and soil fertility levels. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As a key factor influencing farming activities, sowing time is highly associated with cereal grain yield and quality around the world (Bajaj et al, 2008;Wang et al, 2018). Previous studies have demonstrated sowing time is closely related to agro-meteorological factors, such as effective accumulated temperature, precipitation photosynthetic active radiation, even nutrient uptake (Gaile 2012;Verma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key factor influencing farming activities, sowing time is highly associated with cereal grain yield and quality around the world (Bajaj et al, 2008;Wang et al, 2018). Previous studies have demonstrated sowing time is closely related to agro-meteorological factors, such as effective accumulated temperature, precipitation photosynthetic active radiation, even nutrient uptake (Gaile 2012;Verma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Costabr et al, (2013) reported sowing date, varieties and seeding rate significantly affected test weight in bread wheat plants, and grain test weight with delayed sowing showed decrease tends under irrigated Mediterranean systems, and the similar result was also found by Ozturk et al, (2010) in Erzurum (Turkey) dryland conditions. And, the changing in grain qualities by delayed sowing date are related to duration of critical periods for growth or crop establishment, especially for grain filling, but also to genetic and the changes of environmental conditions (Jaliya et al, 2008;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%